Effect of a one-week spiritual retreat on dopamine and serotonin transporter binding: a preliminary study. Issue 3 (3rd July 2018) - Newberg, Andrew B.; Wintering, Nancy; Yaden, David B.; Zhong, Li; Bowen, Brendan; Averick, Noah; Monti, Daniel A.
ABSTRACT: Spiritual retreats are a commonly used intensive program of meditation and prayer, along with other elements, designed to provide participants with opportunities for spiritual and psychological growth. While individual elements of such retreats have been studied, there have been no reports in the literature regarding the neurophysiological effects of these retreats. This preliminary study presents the first data we are aware of on the neurophysiological effects, particularly those related to dopamine and serotonin, in a group of participants undergoing an intensive seven-day spiritual retreat. We used DaTscan single photon emission computed tomography (SPECT) in 14 individuals before and closely following participation in a seven-day spiritual retreat. We observed significant decreases in dopamine transporter binding in the basal ganglia and significant decreases in serotonin transporter binding in the midbrain after the retreat program. Participating in the retreat also resulted in significant changes in a variety of psychological and spiritual measures. We also report the relationship between neurophysiological and subjective measures along with a discussion of potential methodological challenges for future studies.